Fuzzy-based smart system for controlling road lights - Satam, Ihab Abdulrahman (Vojnotehnički glasnik / Military Technical Courier, 2022)
Introduction: The energy consumed for street lighting is a major expenditure in urban environments. According to the World Bank, it constitutes up to 65% of cities' electricity costs and 10% of their overall budgets. The demand for lighting is growing significantly due to rapid urbanization, thus eating up even more energy and money - unless smarter solutions are deployed to reduce costs.Method:  In this paper, a model for street lighting was established, consisting of several lamp posts on both sides of the street. The model was the exact replica of the street lighing system inside the city of Kirkuk, Iraq. The number of objects passing along the street was monitored, both during and out of rush hours.This all was taken into account in the energy consumption calculation. The controller used for this model is Arduino UNO. The Arduino receives signals from 3 IR sensors, processes these signals, and then sends the action to the lamp posts. Fuzzy logic was applied in two cases: the first one is during the daylight, the second one is during the sunrise and the sunset, to control the intensity of the light of the lamp posts.Results:  Both cases showed significant results regarding the reliability, efficiency, and countability of the system in decreasing the level of energy consumption.Conclusion: The system can be applicable for smart city projects. It is efficient, cost effective and shows reliable results in saving energy.
Keywords: fuzzy logic; arduino; smart street lighting; energy consumption; road lights